Attitudes towards the job potential of adult educable mentally retarded - Felipe, Iluminada S.
The study was undertaken to determine the attitudes of Special Education and Non-Special Education (SPED) parents, teachers, and employers toward the job potential of the adult educable mentally retarded (AEMR). The objectives were to determine whether significant differences exist between the attitudes of SPED and NON-SPED parents, teachers and employers; to find out whether they agree that the AEMR can work; to determine whether SPED parents are willing to let their mentally retarded children hold jobs; and to investigate whether employers are willing to hire the AEMR.